THE USE OF GANGLIOSIDES IN THE COMPLEX TREATMENT OF ISCHEMIC STROKE IN THE ELDERLY - Vakhabova, N.M (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To evaluate the effectiveness of a new group of neurocytoprotectors – gangliosides in the treatment of patients with acute ischemic stroke. Material and methods: Under observation, there were 25 patients (13 (52.0%) men and 12 (48.0%) women, average age 61.9±0.6 years) who received the Mavix drug (1st gr.), and 25 patients (14 (56.0%) men and 11 (44.0%) women, average age 62.7±0.5 years) who used the basic method of treating ischemic stroke (2nd gr.). Results: Introduction to the treatment program for ischemic stroke «Mavix» injection solution 20 mg / 2 ml manufactured by «Jilin Qijian Bio-Pharmaceutical Co. Ltd. ”led to a reduction in symptoms of damage to the cranial nerves, sensory disturbances, pyramidal symptoms, changes in muscle tone and speech disorders by the 21st day of treatment. Conclusions: The additional appointment of gangliosides has been shown to be highly effective in the treatment of acute ischemic stroke.